2011
DOI: 10.1021/jf204539v
|View full text |Cite
|
Sign up to set email alerts
|

Banana (Musa sp. var. elakki bale) Flower and Pseudostem: Dietary Fiber and Associated Antioxidant Capacity

Abstract: Banana flower (BF) and pseudostem (PS) are byproducts of banana cultivation and are known to have health beneficial effects. The main objective of this study was to evaluate the dietary fiber composition and antioxidant effect of BF and PS. In the present study, BF and PS were found to be rich in dietary fiber (65.6 ± 1.32 and 28.8 ± 0.98%, respectively). Dietary fiber fractions were extracted and characterized in terms of sugar profile, and antioxidant activities were determined. BF and PS fractions were rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 33 publications
3
53
3
4
Order By: Relevance
“…These values were higher than the control bread (BCtr, 6.97%). This can be attributed to the fact that banana pseudo-stem contains good amount of neutral sugars as detailed above (Bhaskar et al, 2011). Hence, this is expected to contribute to pentosan content rise in composite breads.…”
Section: Total Sugars Total Pentosans and Soluble Pentosanmentioning
confidence: 97%
See 1 more Smart Citation
“…These values were higher than the control bread (BCtr, 6.97%). This can be attributed to the fact that banana pseudo-stem contains good amount of neutral sugars as detailed above (Bhaskar et al, 2011). Hence, this is expected to contribute to pentosan content rise in composite breads.…”
Section: Total Sugars Total Pentosans and Soluble Pentosanmentioning
confidence: 97%
“…According to Cordeiro, Belgacem, Torres, & Moura (2004), glucose (74%) is the predominant monosaccharide present in the banana pseudo-stem and this is then followed by xylose (13.1%), arabinose (9.1%), galactose (2.5%) and mannose (1.3%). Previously, banana pseudostem has been reported to contain a good amount of neutral sugars [glucose (87.0%), xylose (8.3%), and arabinose (4.5%)] (Bhaskar, Mahadevamma, Chilkunda, & Salimath, 2011). The observed increase in sugar content in composite breads can be attributed to the starch hydrolysis that occurs during fermentation (Dhingra and Jood, 2001).…”
Section: Total Sugars Total Pentosans and Soluble Pentosanmentioning
confidence: 99%
“…From a previous study done on the same banana species it was shown that banana blossom is a rich source of dietary fibre, unsaturated fatty acids, vitamin E, total saponins, and flavonoids [5]. These data suggested that polyphenol rich dietary fibres in banana blossom may modulate the lipid metabolism in rats [15]. In this way, several studies have suggested that antioxidant rich dietary fibre may have a positive effect on cardiovascular disease risk factors [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, chloroform, water, and ethanol extract of another banana variety ( Musa sapientum ) flowers were found to exhibit hypoglycaemic activity in alloxan diabetic rat [1214]. Hemicellulose fraction of Musa sapientum showed high amounts of total polyphenols and total antioxidants [15], indicating that banana blossom is a rich source of dietary fibre associated with polyphenols, which could promote health benefits. As the dietary fibre consumption is alarmingly low, it is important to investigate the potential of underutilized vegetables as potent antioxidants and blood lipid lowering agents.…”
Section: Introductionmentioning
confidence: 99%
“…In the flowers of Musa spp., phenolic acids such as gallic acid, catechol, protocatechuic acid, gentisic acid, vanillic acid, caffeic acid, syringic acid, p‐coumaric acid, ferulic acid and epicatechin have been identified . These compounds have inhibitory activity on enzymes such as α‐amylase and aldose reductase, contributing to the reduction in glycaemic levels and the prevention of complications .…”
Section: Introductionmentioning
confidence: 99%